Effectiveness of Planned Health Teaching on Knowledge of Anganwadi Workers Regarding Prevention of Worm Infestation among Under-five Children at Selected Anganwadi - Pagare, Ashwini; Deshpande, Rupali; Shinde, Ekta; Gurav, Arundhati; D’souza, Florance (Indian Journal of Nursing Sciences, 2024)
Aim of Study: The aim of the present study is to assess the effectiveness of planned health teaching on the knowledge of anganwadi workers regarding prevention of worm infestation among under-five children at selected Anganwadi”. Materials and Methods: Quantitative research approach with Quasi-Experimental research design, one-group pretestposttest design was used for the study. A total of 60 anganwadi workers were selected by using the purposive sampling technique (non-probability technique). That 60 samples were equally divided into three groups each group containing 20 samples. Data were collected using structured knowledge questionnaires. Two groups are covered on the same day and divided them in morning and evening session, Third group on next day. Structured knowledge questionnaire also administered on the same day following the pre-test in each group on each day according to distribution. After 7 days, post-test was conducted to assess the gain in knowledge using the same structured knowledge questionnaire. Result: Results showed that there has been increase in knowledge of Anganwadi Workers after the administration of planned health teaching. In post-test knowledge mean score of 25.5 was higher than their pre-test mean score of 14.5. About 71.67% of the anganwadi workers had scored marks within very good category. The mean difference of pre-test and post-test knowledge scores was 11. Calculated “t” value is 29.54 at significant difference of 59 which is considered to be statistically significant at 0.05 level of significance, Thus, null hypothesis H0 is rejected and research hypothesis H1 is accepted which conclude that planned health teaching was effective in improving the knowledge of anganwadi workers regarding prevention of worm infestation. Conclusion: Thus study revealed that in pre-test knowledge mean score was 14.5, whereas in post-test knowledge mean score was found to be increased up to 25.5 Hence, it is concluded that planned health teaching was effective in improving knowledge of Anganwadi workers.